Photooxidation chlorinated hyhdrocarbon using TiO2 thin film - Ng, Sook Chuin; Othman, Mohd. Yusuf; Wan Abu Bakar, Wan Azelee; Mohd. Saiyudi, Noor Khaida Wati (Malaysian Society of Analytical Sciences, 2005)
The gas phase photooxidation of chloroform, dichlo romethane and carbon tetrachloride were investigated using doped and undoped TiO 2 thin film irradiated by UV light with maximum wavelength at 354 nm. Thin films TiO 2 coated on pyrex glass cylinders were prepared using the sol-gel dip coating technique. In this research, the dopants used were Mn 2+ , Fe 2+ and Fe 3+ . The M n 2+ and Fe 2+ -doped TiO 2 were prepared with 1:0.01 , 1 :0.00 5, 1:0 .001, 1:0 .0005 and 1 :0.000 3 atomic ratios. Meanwhile, Fe 3+ -doped TiO 2 were prepared with 1 :0.001 , 1:0.0005 and 1 :0.0003 atomic ratios. In order to determine the optimum do pant ratio, photo oxidation of dichloromethane, chloroform and carbon tetrachloride were conducted using all catalyst samples. Mn 2+ , F e 3+ and Fe 2+ doped catalysts have an optimum ratio of 1:0.0005 . The addition of Fe 2+ and Fe 3+ into TiO 2 increased the photooxidation of chloroform, carbon tetrachloride and dichloromethane. Mn 2+ is detrimental to the photooxidation of carbon tetrachloride, dichloro methane and carbon tetrachloride. Therefore, although dopants affect the photoactivity of TiO 2, the effects due to the type and concentration of dopants and VOCs used can not be ignored.